Noise and Epigenetic Inheritance of Single-Cell Division Times Influence Population Fitness - Cerulus, Bram; New, Aaron M.; Pougach, Ksenia; Verstrepen, Kevin J. (Current biology, 2016)
The fitness effect of biological noise remains unclear. For example, even within clonal microbial populations, individual cells grow at different speeds. Although it is known that the individuals’ mean growth speed can affect population-level fitness, it is unclear how or whether growth speed heterogeneity itself is subject to natural selection. Here, we show that noisy single-cell division times can significantly affect population-level growth rate. Using time-lapse microscopy to measure the division times of thousands of individual S. cerevisiae cells across different genetic and environmental backgrounds, we find that the length of individual cells’ division times can vary substantially between clonal individuals and that sublineages often show epigenetic inheritance of division times. By combining these experimental measurements with mathematical modeling, we find that, for a given mean division time, increasing heterogeneity and epigenetic inheritance of division times increases the population growth rate. Furthermore, we demonstrate that the heterogeneity and epigenetic inheritance of single-cell division times can be linked with variation in the expression of catabolic genes. Taken together, our results reveal how a change in noisy single-cell behaviors can directly influence fitness through dynamics that operate independently of effects caused by changes to the mean. These results not only allow a better understanding of microbial fitness but also help to more accurately predict fitness in other clonal populations, such as tumors. [Display omitted] •Single-cell division times of yeast strains were measured in different conditions•Individual cells show noise and epigenetic inheritance of division times•For a given mean division time, noise and epigenetic phenomena increase fitness•Catabolic gene expression can contribute to division time noise and epigenetics The fitness effect of growth noise is poorly understood. Cerulus et al. show that certain yeast populations can show high variability and epigenetic inheritance of division times. Mathematical modeling shows that, for a given mean, increasing these traits increases the population growth rate. These traits are linked to catabolic gene expression.